Intervaltraining Training Methods On The VO2MAX Results Of Lubuk Linggau City Athletics Athletes - Ilham Kurniawan; Daryono Daryono; Puput Sekar Sari (International Journal of Studies in International Education, 2024)
Sport is a medium for people to gather and has become a new necessity in life. One of the most popular sports that many compete in is athletics. VO2Max is one of the supporting achievements of athletes, especially branch athletes who require good physical condition. Based on information from the management of the Indonesian Athletics Association in the city of Lubuklinggau, athlete performance tends to decline from the 2019 Provincial Sports Week in Prabumulih City where athletes running the 1,500m middle distance did not achieve good results. , athletes were only able to finish in 10th and 13th place. In the research used, this was experimental research using a one group pretest posttest design, where this research method was used to look for cause and effect or the influence of one variable on another variable. The population of this study were all 10 athletic athletes from the city of Lubuklinggau. The sampling technique was random sampling. This research involved 10 athletic athletes from the city of Lubuklinggau with 16 treatments in the form of interval training exercises, giving results where the average VO2Max before was 42.15 which changed to 44.12 after being given interval training treatment. Meanwhile, the results of scientific tests through the paired sample t test show that there is an influence of interval training on the VO2Max results of Lubuk Linggau City athletic athletes because the tcount is (5.625 - 1.833). Based on the findings of the research results above, this research can be concluded that the average VO2Max before was 42.15 which changed to 44.12 after being given interval training treatment. The results of statistical tests using the paired sample t test show that there is an influence of interval training on the VO2Max results of Lubuk Linggau City athletic athletes.